DIRECTIONS FOR IMPROVING THE ORGANISATIONAL SYSTEM OF VALUE-BASED MANAGEMENT IN A HIGH-TECH COMPANY - Vitaliy Zakharchenko; Svitlana Yermak (Izdevnieciba "Baltija Publishing", 2022)
The purpose of the article is to formulate directions for improving the organisational system of value-based management in a high-tech company. Methodology. The methods of analysis and synthesis, comparison and grouping, conceptualisation, strategic analysis and business process reengineering were the methodological basis of the research. Results. The conditions under which it is possible for Ukrainian high-tech enterprises to withstand competition, to survive, to develop, to be in the process of self-improvement, in a state of constant search for new organisational forms of functioning and technologies, new strategies of functioning, new types of products and new areas of application of products are defined. The methods of existence of high-tech companies are determined - the concept of survival and the concept of breakthrough. Within the framework of creation of modern organisational and technological systems three basic types of general business strategies are proposed - leadership, differentiation, focusing. For the modern practice of value-oriented management of innovative production from the point of view of intra-company management, the main characteristics are defined - functional, process, system, elemental. The organisational management of a high-tech enterprise when creating modern organisational and technological systems must take into account the following types of modernisation: technological, social, institutional, cultural. At the same time, possible ways of restructuring the enterprise are determined. The life activity of a high-tech enterprise is analysed in relation to its business processes and business functions. In general, the change in the goals and orientation of high-tech production is reflected in the content of the management concept and management structures, as the scope of cost analysis tasks related to the search for optimal conditions for the production and sale of goods, economic risk assessment and forecasting the behaviour of competitors is expanding. There is a need for infrastructural changes determined by the organisation and functioning of special units focused on the system of strategic planning and organisational support of decisions. Value/originality. A model of the organisation of intra-firm management in a high-tech enterprise is proposed by optimising the value-oriented management system of a high-tech enterprise, taking into account the complexity of the modern production system, its heterogeneity, the changeability of its elements, the structural diversity and the variety of links between them.